Architectural Patterns : Uncover essential patterns in the most indispensable realm of enterprise architecture /: Uncover essential patterns in the most indispensable realm of enterprise architecture. (2017) - Chelliah, Pethuru Raj; J, Harihara Subramanian; Murali, Anupama
No abstract available